Aberrant T Cell Signaling and Subsets in Systemic Lupus Erythematosus - Katsuyama, Takayuki; Tsokos, George C.; Moulton, Vaishali R. (Frontiers in Immunology, 2018)
Systemic lupus erythematosus (SLE) is a chronic multi-system debilitating autoimmune disease, which mainly afflicts women in the reproductive years. A complex interaction of genetics, environmental factors and hormones results in the breakdown of immune tolerance to ‘self’ leading to damage and destruction of multiple organs such as the skin, joints, kidneys, heart and brain. Both innate and adaptive immune systems are critically involved in the misguided immune response against self-tissues. Dendritic cells, neutrophils and innate lymphoid cells are important in initiating antigen presentation and propagating inflammation at lymphoid and peripheral tissue sites. Autoantibodies produced by B lymphocytes, and immune complex deposition into vital organs contribute to tissue damage. T lymphocytes are increasingly being recognized as key contributors to disease pathogenesis. CD4 T follicular helper cells enable autoantibody production, inflammatory Th17 subsets promote inflammation, while defects in regulatory T cells lead to unchecked immune responses. A better understanding of the molecular defects including signaling events and gene regulation underlying the dysfunctional T cells in SLE is necessary to pave the path for better management, therapy and perhaps prevention of this complex disease. In this review, we focus on the aberrations in T cell signaling in SLE and highlight therapeutic advances in this field.